Host STING-dependent MDSC mobilization drives extrinsic radiation resistance. Issue 1 (December 2017) - Liang, Hua; Deng, Liufu; Hou, Yuzhu; Meng, Xiangjiao; Huang, Xiaona; Rao, Enyu; Zheng, Wenxin; Mauceri, Helena; Mack, Matthias; Xu, Meng; Fu, Yang-Xin; Weichselbaum, Ralph
Abstract Radiotherapy induces and promotes innate and adaptive immunity in which host STING plays an important role. However, radioresistance in irradiated tumors can also develop, resulting in relapse. Here we report a mechanism by which extrinsic resistance develops after local ablative radiation that relies on the immunosuppressive action of STING. The STING/type I interferon pathway enhances suppressive inflammation in tumors by recruiting myeloid cells in part via the CCR2 pathway. Germ-line knockouts of CCR2 or treatment with an anti-CCR2 antibody results in blockade of radiation-induced MDSC infiltration. Treatment with anti-CCR2 antibody alleviates immunosuppression following activation of the STING pathway, enhancing the anti-tumor effects of STING agonists and radiotherapy. We propose that radiation-induced STING activation is immunosuppressive due to (monocytic) M-MDSC infiltration, which results in tumor radioresistance. Furthermore, the immunosuppressive effects of radiotherapy and STING agonists can be abrogated in humans by a translational strategy involving anti-CCR2 antibody treatment to improve radiotherapy. Tumors often develop resistance to radiotherapy. Here the authors show that irradiation leads to a CCR2-dependent infiltration by myeloid derived suppressor cells that promote radio-resistance through inhibition of adaptive immune responses and that the use of CCR2 antibodies in mice reduces such resistance.